Ventilation Strategy for Proper IAQ in Existing Nurseries Buildings - Lesson Learned from the Research during COVID-19 Pandemic - Katarzyna Ratajczak (Aerosol and Air Quality Research)
Abstract During the COVID-19 pandemic, many recommendations were made in the field of limiting the transmission of the SARS-CoV-2 virus, from which we can learn a lesson for determining ventilation strategies in strategic types of buildings (those whose closure during a pandemic is harmful to the economy, e.g., nurseries). The research was aimed at identifying recommendations in the field of ventilation and proposing a solution that would be applicable in existing buildings intended for the care of small children, and which would ensure the proper quality of the building environment, at the same time with low costs incurred by the owners. The outside air pollution (PM10) and the climate in winter (low air temperature) were also taken into account. A strategy was proposed based on the use of decentralized units, dedicated to single rooms, thanks to which the appropriate amount of air is supplied (per person), the air is cleaned and heated in the heat recovery exchanger. It has been shown that the use of heat recovery ensures that the costs of air heating will be significantly lower than during airing. The proposed solutions require two holes in the external wall with a diameter of 160–200 mm (depending on the number of people), which guarantees the technically possible application in existing buildings. The strategy provides suitable conditions for the functioning of nurseries, but can be used in many types of buildings, in cold and temperate climates, where airing of the rooms during winter is not possible, especially in the case of locations where the quality of outdoor air is very poor. The proposed strategy may be applied during a pandemic, but also on a daily basis, because by ensuring the proper quality of indoor air, young children will have healthy and hygienic conditions for development when they are not at home.